Faktor Yang Mempengaruhi Struktur Modal Perusahaan Sub Sektor Pertambangan Batubara Yang Terdaftar Di Bursa Efek Indonesia - Jannati Tangngisalu; Ervina Ervina; Muhammad Irfai Sohilauw (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to analyze the relationship between asset growth and profitability on the capital structure of coal mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Collecting data using secondary data, with purposive sampling technique. The data analysis method uses multiple linear regression techniques using E-views version 10 software. The results show that asset growth has a significant positive effect on capital structure, and profitability does not affect capital structure.